A new species of Sweltsa (Plecoptera: Chloroperlidae) from China, with a key to the Sweltsa males of China - Chen, Zhi-Teng; Du, Yu-Zhou (Zootaxa, 2017)
A new species of the alloperline genus Sweltsa, Sweltsa hamula sp. nov. is described and illustrated from Sichuan Province of southwestern China. The male of the new species is distinguished from other known Chinese Sweltsa species by the hook-shaped apex of the epiproct. A provisional key is presented to the known Sweltsa males from China.